2015
DOI: 10.3390/v7072792
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in Chikungunya Virus Infection—From Virus CellBinding to Membrane Fusion

Abstract: Chikungunya virus (CHIKV) is a rapidly emerging mosquito-borne alphavirus causing millions of infections in the tropical and subtropical regions of the world. CHIKV infection often leads to an acute self-limited febrile illness with debilitating myalgia and arthralgia. A potential long-term complication of CHIKV infection is severe joint pain, which can last for months to years. There are no vaccines or specific therapeutics available to prevent or treat infection. This review describes the critical steps in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 182 publications
(292 reference statements)
3
100
0
11
Order By: Relevance
“…Further, they also concluded that Fig. 3 The secondary structure of E2 protein generated using the Psipred server Potential entry inhibitors of the envelope protein (E2) of Chikungunya virus: in silico… 43 this mutation at 211 position is probably involved in binding of the E2 protein with the receptor on the host cell [41]. Glycosaminoglycans (GAGs) are polymers of disaccharide units that are associated with the outer surface of mammalian cells where they act as virus receptors.…”
Section: Mutational Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Further, they also concluded that Fig. 3 The secondary structure of E2 protein generated using the Psipred server Potential entry inhibitors of the envelope protein (E2) of Chikungunya virus: in silico… 43 this mutation at 211 position is probably involved in binding of the E2 protein with the receptor on the host cell [41]. Glycosaminoglycans (GAGs) are polymers of disaccharide units that are associated with the outer surface of mammalian cells where they act as virus receptors.…”
Section: Mutational Analysismentioning
confidence: 99%
“…Both CHIKV and DENV are spread by Aedes aegypti and Aedes albopictus mosquitoes [3]. CHIKV is endemic in many parts of the world including Africa, Asia and tropical regions of America [43]. Nearly 94 countries were identified with substantial CHIKV infection in a recent investigation [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). With less frequency, the virus can affect the liver or cause encephalopathy, encephalitis, myocarditis, and heart blockage 27 . Although 5-15% of individuals suffer from asymptomatic infection 26 , the rest generally develop symptoms that progress from the acute to the chronic phase 25 .…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…Chronic symptomatology is observed with greater frequency in persons over 60 years of age that have very high viremia (> 10 10 PFU/ml) during the acute phase of the disease 27 . The infection is initially very rapid and the virus is typically eliminated 5-7 days after onset of the fever.…”
Section: Pathogenesis Of Chikungunya Virus Diseasementioning
confidence: 99%